A companion to Renaissance poetry - Bates, Catherine, 1964- (Blackwell companions to literature and culture, 2018)
"The most comprehensive collection of essays on Renaissance poetry on the market Covering the period 1520-1680, A Companion to Renaissance Poetry offers 46 essays which present an in-depth account of the context, production, and interpretation of early modern British poetry. It provides students with a deep appreciation for, and sensitivity toward, the ways in which poets of the period understood and fashioned a distinctly vernacular voice, while engaging them with some of the debates and departures that are currently animating the discipline. A Companion to Renaissance Poetry analyzes the historical, cultural, political, and religious background of the time, addressing issues such as education, translation, the Reformation, theorizations of poetry, and more. The book immerses readers in non-dramatic poetry from Wyatt to Milton, focusing on the key poetic genres--epic, lyric, complaint, elegy, epistle, pastoral, satire, and religious poetry. It also offers an inclusive account of the poetic production of the period by canonical and less canonical writers, female and male. Finally, it offers examples of current developments in the interpretation of Renaissance poetry, including economic, ecological, scientific, materialist, and formalist approaches. • Covers a wide selection of authors and texts • Features contributions from notable authors, scholars, and critics across the globe • Offers a substantial section on recent and developing approaches to reading Renaissance poetry A Companion to Renaissance Poetry is an ideal resource for all students and scholars of the literature and culture of the Renaissance period."--EBSCO.